Developing an efficient phase-matched attenuation correction method for quiescent period PET in abdominal PET/MRI - Yang, Jaewon (Phys Med Biol, 2018)
Respiratory motion causes misalignments between positron emission tomography (PET) and magnetic resonance (MR)-derived attenuation maps (μ-maps) in addition to artifacts on both PET and MR images in simultaneous PET/MRI for organs such as liver that can experience motion of several centimeters. To address this problem, we developed an efficient MR-based attenuation correction (MRAC) method to generate phase-matched μ-maps for quiescent period PET (PET(Q)) in abdominal PET/MRI. MRAC data was acquired with CIRcular Cartesian UnderSampling (CIRCUS) sampling during 100 s in free-breathing as an accelerated data acquisition strategy for phase-matched MRAC (MRAC(PM-CIRCUS)). For comparison, MRAC data with raster (Default) k-space sampling was also acquired during 100 s in free-breathing (MRAC(PM-Default)), and used to evaluate MRAC(PM-CIRCUS) as well as un-matched MRAC (MRAC(UM)) that was un-gated. We purposefully oversampled the MRAC(PM) data to ensure we had enough information to capture all respiratory phases to make this comparison as robust as possible. The proposed MRAC(PM-CIRCUS) was evaluated in 17 patients with (68)Ga-DOTA-TOC PET/MRI exams, suspected of having neuroendocrine tumors or liver metastases. Effects of CIRCUS sampling for accelerating a data acquisition were evaluated by simulating the data acquisition time retrospectively in increments of 5 s. Effects of MRAC(PM-CIRCUS) on PET(Q) were evaluated using uptake differences in the liver lesions (n = 35), compared to PET(Q) with MRAC(PM-Default) and MRAC(UM). A Wilcoxon signed-rank test was performed to compare lesion uptakes between the MRAC methods. MRAC(PM-CIRCUS) showed higher image quality compared to MRAC(PM-Default) for the same acquisition times, demonstrating that a data acquisition time of 30 s was reasonable to achieve phase-matched μ-maps. Lesion update differences between MRACPM-CIRCUS (30 s) versus MRAC(PM-Default) (reference, 100 s) were 0.1% ± 1.4% (range of −2.7% to 3.2%) and not significant (P > .05); while, the differences between MRAC(UM) versus MRAC(PM-Default) were 0.6% ± 11.4% with a large variation (range of −37% to 20%) and significant (P < .05). In conclusion, we demonstrated that a data acquisition of 30 s achieved phase-matched μ-maps when using specialized CIRCUS data sampling and phase-matched μ-maps improved PET(Q) quantification significantly.